The Relevance and Problems of Entrepreneurial Competence Development in Vocational Training System - Chepel, Vladimir F.; Nikitin, Aleksandr A.; Palyanov, Mikhail P.; Ovchinnikov, Vladislav A.; Temerbekova, Albina A. (International Review of Management and Marketing, 2016)
The article substantiates the necessity of education system transition to mass instruction of entrepreneurial competences development. The problem of entrepreneurial competence development is recognized as being of great importance since it is associated with the transition process to a new structure of industrial relation between small and big business at the end of XX century. The leading approach is the analysis of current situation in economy and education system in various countries concerning the demand for entrepreneurial competences development. The authors define purposes, conditions, principles and approaches used to design, develop and implement a teaching, organizational and methodological package. This package will be an efficient supplement to the existing teaching aids in the system of higher and secondary vocational education. The authors determined some particular priority guidelines associated with the investigations of the specified problem which should be included in the range of scientific and pedagogical objectives and offered some issues for further discussion and collaboration. Keywords: Entrepreneurial Competences, Training, Organizational and Methodological Package, Vocational Education JEL Classifications: I21, I25, I28